THE LEVEL OF MENTAL STRESS, AND SELF - ESTEEM OFCHILDREN’S HEALTH WITH CHRONIC KIDNEY DISEASE - I.S. Dryl; A.F. Shipko; T.F. Kolfbaeva; L.K. Petrenko; I.V. Zabashta (Ukrainian Journal of Nephrology and Dialysis, 2015)
The most frequent mental changes in children can include increased anxiety, depression, aggression and anger, the existence of which may contribute to the progression of physical illness.Materials and methods. The study involved 49 children aged 7 to 17 years (mean age 12,7 ± 3,1let) with chronic kidney disease. Further assess psychological stress based on the level of anxiety, aggression, anger, and depression.Results. In assessing the level of anxiety, aggression, anger, and depression in all groups of children prevailed with the average of 73,1 ± 7% to 87,8 ± 5,1% of children in the group. At 24,3 ± 7% of children identified elevated levels of aggression, half of whom had congenital abnormalities of the urinary system. Most children 38 (86,3 ± 5,2%) level of depression was within average. Established cases of depression to improve small, moderate and significant among girls 13,5 ± 1,5years, which amounted to 13,6 ± 5,2% of children.Conclusions. The most vulnerable are children, particularly girls with chronic kidney disease on the background of congenital anomalies of the urinary system. All children with chronic kidney disease is necessary to evaluate the level of mental strain for the optimization of measures to prevent recurrence of the disease and improve the quality of life ofchildren.